2016
DOI: 10.1155/2016/9846731
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of NTPDase-1 fromTrypanosoma cruziand Development of an Online Label-Free Assay

Abstract: The use of IMERs (Immobilized Enzyme Reactors) as a stationary phase coupled to high performance chromatographic systems is an interesting approach in the screening of new ligands. In addition, IMERs offer many advantages over techniques that employ enzymes in solution. The enzyme nucleoside triphosphate diphosphohydrolase (NTPDase-1) from Trypanosoma cruzi acts as a pathogen infection facilitator, so it is a good target in the search for inhibitors. In this paper, immobilization of NTPDase-1 afforded ICERs (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
(49 reference statements)
0
3
0
2
Order By: Relevance
“…From in vitro evidence, it is understandable that ecto -NTPDase has been considered a promising molecular target in the treatment of Chagas disease [ 10 , 37 , 38 ]. However, in vitro studies also showed a contradictory response.…”
Section: Discussionmentioning
confidence: 99%
“…From in vitro evidence, it is understandable that ecto -NTPDase has been considered a promising molecular target in the treatment of Chagas disease [ 10 , 37 , 38 ]. However, in vitro studies also showed a contradictory response.…”
Section: Discussionmentioning
confidence: 99%
“…Different solid supports can be employed for enzyme immobilization in the development of LC-based on-flow screening assays. Silica-based supports (de Moraes et al, 2012Vanzolini et al, 2013;da Silva et al, 2013;Hu et al, 2015;Silva et al, 2015;Vilela et al, 2015Vilela et al, , 2018Calil et al, 2016;Magalhães et al, 2016;Sarria et al, 2016;Ferreira Lopes Vilela and Cardoso, 2017;Cornelio et al, 2018;Lima et al, 2019;Medina et al, 2019;Qian et al, 2019;Seidl et al, 2019Seidl et al, , 2022Ferey et al, 2019;Chapla et al, 2020;Hou et al, 2020;de Castro et al, 2022) present a versatile and largely explored motif due presence of many hydroxyl groups on its surface. For example, those groups are readily reactive with 3aminopropyltriethoxysilane (APTES), furnishing an amine- rich surface that can further react with glutaraldehyde (GA), yielding a terminal reactive aldehyde surface susceptible reactions with nucleophilic groups present on the enzyme surface (Figure 2B).…”
Section: Solid Supports For Enzyme Immobilization In the Development ...mentioning
confidence: 99%
“…Zonal elution has also been applied to monitor on-line enzyme activity in ligand screening assays, resulting in reliable and specific assays that allow the biocatalysis product to be directly quantified (da Silva et al, 2012; de Moraes et al, 2013; Calil et al, 2016; Lima et al, 2016; Magalhães et al, 2016; Ferreira Lopes Vilela and Cardoso, 2017; Cornelio et al, 2018; Vilela et al, 2018; Seidl et al, 2019). This approach prevents interferences in inhibitors screening and furnishes reliable data concerning the substrate- and inhibitor-enzyme binding.…”
Section: On-line Approachesmentioning
confidence: 99%